2020
DOI: 10.1158/1055-9965.epi-19-1060
|View full text |Cite
|
Sign up to set email alerts
|

Association of Imaging-Based Body Fat Distribution and Mammographic Density in the Multiethnic Cohort Adiposity Phenotype Study

Abstract: Background: As the stronger association of obesity with postmenopausal breast cancer in Asian than white women may be due to body fat distribution, we examined the relation of adiposity measures with percent mammographic density (PMD), a strong predictor of breast cancer incidence.Methods: A total of 938 women from five ethnic groups (69.1 AE 2.7 years) in the Adiposity Phenotype Study (APS) underwent DXA and MRI imaging. PMD was assessed in routine mammograms using a computer-assisted method. Spearman correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Recent large-scale studies of breast cancer patients found prognostic value in the presence of clinically non-evident muscle wasting detected with routine CT scans for staging, even in nonmetastatic patients and in a setting of changes of subcutaneous adipose tissue [18,19]. Other studies have investigated the prognostic value of body composition in association with metabolic risk factor profiles or adipokine levels, and found it added value to clinical decision making and showed a prognostic impact [20][21][22]. Thus, imaging appears to be able to contribute predictive information that might not otherwise be accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Recent large-scale studies of breast cancer patients found prognostic value in the presence of clinically non-evident muscle wasting detected with routine CT scans for staging, even in nonmetastatic patients and in a setting of changes of subcutaneous adipose tissue [18,19]. Other studies have investigated the prognostic value of body composition in association with metabolic risk factor profiles or adipokine levels, and found it added value to clinical decision making and showed a prognostic impact [20][21][22]. Thus, imaging appears to be able to contribute predictive information that might not otherwise be accessible.…”
Section: Introductionmentioning
confidence: 99%